2021
DOI: 10.1007/s10560-021-00756-x
|View full text |Cite
|
Sign up to set email alerts
|

Migration Intentions and Alcohol Use Among Adolescents in West-Central Mexico

Abstract: This study explores the association between migration intentions and alcohol use among west-central Mexico adolescents living in high migration communities. This study used the baseline data from the Family Migration and Early Life Outcomes (FAMELO) project (N = 1286), collected in 2018. We used multiple imputations to address missingness and propensity score matching to reduce the selection bias. We also conducted subgroup analyses to compare gender difference (i.e., boys vs. girls) on the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
5
0
0
Order By: Relevance
“…Interestingly, from the studied health related behaviors in relation to post-pandemic emigration plans, it was also found that adolescents who reported alcohol consumption were over 2 times more likely to report post-pandemic emigration plans than those who did not report alcohol consumption in this study. This study contributes to the previous findings focused on the migration intentions and alcohol use (Marsiglia, Wu, Han et al, 2021), on the understanding pre-departure migrationhealth associations (Gushulak & MacPherson, 2011), and the results of this study support the hypothesis of self-selection of young people likely to use alcohol into pre/migrant group (Borges, G., Breslau, J., Orozco et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, from the studied health related behaviors in relation to post-pandemic emigration plans, it was also found that adolescents who reported alcohol consumption were over 2 times more likely to report post-pandemic emigration plans than those who did not report alcohol consumption in this study. This study contributes to the previous findings focused on the migration intentions and alcohol use (Marsiglia, Wu, Han et al, 2021), on the understanding pre-departure migrationhealth associations (Gushulak & MacPherson, 2011), and the results of this study support the hypothesis of self-selection of young people likely to use alcohol into pre/migrant group (Borges, G., Breslau, J., Orozco et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…A gender dimension to migration intentions, aspirations was confirmed (Marsiglia, Wu, Han et al, 2021). Accordingly, the results of this study showed girls' higher level of study abroad intention and a larger percentage of girls also reported post-pandemic emigration plans.…”
Section: Discussionsupporting
confidence: 65%
“…The results of this study support the hypothesis of self-selection of young people likely to use alcohol into a pre-migrant group (Borges et al, 2011) and contribute to previous findings focused on migration intentions and alcohol use (Marsiglia et al, 2021) by improving the understanding of pre-departure migrationhealth associations (Gushulak & MacPherson, 2011). However, the cross-sectional nature of this investigation has limited this understanding and suggested that longitudinal studies are needed for this objective.…”
Section: Discussionsupporting
confidence: 64%
“…The importance of the role of gender in the context of migration intentions and aspirations has been confirmed (Marsiglia et al, 2021). The results of this study showed that girls had higher levels of intention to study abroad.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, a study that explored the relationship between migration intentions and alcohol use in youth living in rural and semi-urban communities from Jalisco, Mexico, showed that youth with migration intentions had significantly higher odds of having used alcohol. This study also reported that adolescents who spoke English as a second language and had intentions to migrate had significantly higher odds of using alcohol [21].…”
Section: The Risk-accumulation Modelsupporting
confidence: 52%